Proximity phenomena in double-barrier structure NbZr/NbOx/Al/AlOy/NbZr - Plecenik, A.; Gazi, S.; Zuzcak, M.; Benacka, S.; Shaternik, V.; Rudenko, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
A tunneling structures NbZr/NbOx/Al/AlOy/NbZr with a thin barrier in the NbZr/NbOx/Al junction and 4 to 6-nm-thick Al interlayer were prepared and studied experimentally. A proximity effect between NbZr and Al through NbOx barrier has been observed. An electrical voltage was generated in the NbOx barrier and a coexistence of the proximity effect and applied voltage in the junction NbZr/NbOx/Al has been observed. This experiment could be described on the basis of a model for coherent charge transport in superconducting/normal proximity structures.